The Influence of Motivation and Work Discipline on Teacher Performance in SMP Negeri 1 Sembawa - Anggreani, Trisna; Fitria, Happy; Missriani (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine the significance of the effect of Motivation and Work Discipline on Teacher Performance in Junior High School Number 1 of Sembawa. This type of research is quantitative descriptive. Samples in the study were 63 respondents wits data collection techniques in the form of a questionnaire (questionnaire). The results showed that: 1) there was a siginificant influence of motivation on teacher performance, 2) there was a significant effect of work discipline on teacher performance, 3) there was a significant effect between motivation and work discipline on teacher performance.